IMPLEMENTASI ANIMASI MATEMATIKA DENGAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION UNTUK MENINGKATKAN PEMAHAMAN MATEMATIS SISWA SD - Lilik Ariyanto; Muhammad Prayito; Ryky Mandar Sary (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2015)
The purpose of this research was to reveal the level of sudents?óÔé¼Ôäó motivation in math learning and also the level of students?óÔé¼Ôäó cognitive using math animation with RME approach. The implementation of math animation with realistic mathemativs education approach had tested before in II-A and II-B class in SDN 3 Palembon, Semarang. The research did four times meeting. The reseacrh method was quasy experiment. The research showed that the score of experiment had completed the academic target by individual nor clasical, and after analyzed, we known that the experiment class had better academic result than control class. Keywords: Implementation, RME, mathematic animation, quasy experiment